Transcriptomic analysis of the upper lip and primary palate development in mice - Cai, Sini; Si, Nuo; Wang, Yanyang; Yin, Ningbei (Frontiers in Genetics, 2023)
Background: Normal fusion of upper lip and primary palate is a complex process involving series of characteristic and orderly regulated cellular events. Cleft lip with or without palate (CL/P), one of the most common congenital malformations, may induced by any of these abnormal events. However, less is known about the precise regulatory process in the fusion of upper lip and primary palate. Methods: Herein, lambdoidal junction tissues of mice from embryonic days 10.5, 11.5 and 12.5, three key fusion stages, were acquired for RNA sequencing. Results: Gene expression profiles in distinct fusion stages of mice were identified. Some differentially expressed genes (DEGs) detected have been reported to affect upper lip and primary palate development. While some DEGs such as Krt5, Pax1, Ambn, Hey2 and Tnmd haven’t been investigated before. Gene set enrichment analysis (GSEA) on DEGs revealed the sequentially intensification of Wnt, PI3K-Akt, MAPK, Hippo and TGF-beta signaling pathways and identified relative highly expressed genes like Tnn, Wnt3a and Wnt16. We also recognized substantial alternative splicing events during the fusion of upper lip and primary palate and identified potential important genes like Gtpbp8, Armcx1, Tle3 and Numa1. Through Protein-protein interaction (PPI) network analysis, we identified series of hub genes, including Col1a2, Fos, Bmp2, Shh, Col1a1, Wnt3a, Anxa1, Gem, and so on. Conclusion: Overall, we provided a comprehensive analysis on the development of upper lip and primary palate. Our work will provide insight into future study of normal upper lip and primary palate development and the etiology of CL/P.